Reproduction of the guava root-knot nematode in Psidium accesses - Castro, José Mauro da Cunha e; Ribeiro, Juliana Martins; Ribeiro Júnior, Pedro Martins; Almeida, Eduardo José de; Sousa, Alain Denis de; Oliveira, Patrícia Gomes de (Comunicata Scientiae, 2017)
The guava decline, a complex disease caused by the interaction between Meloidogyne enterolobii and Fusarium solani, has caused damage to production and unviable guava producing areas in the Lower Basin of the São Francisco Valley. The management of this disease is difficult due to the facts that cultivated plants are susceptible to nematodes, nematicides have no effective control, and the use of fungicides to control Fusarium still has not been evaluated. However, some Psidium genotypes, such as the araçazeiros, show resistance to the nematodes, and therefore decline resistance. The objective of this study was to evaluate the interaction between genotypes of Psidium spp. and M. enterolobii to identify resistant plants. Three araçazeiro genotypes from the states of São Paulo and Paraná were artificially inoculated with M. enterolobii and compared with the species P. guajava cultivar Paluma, which is a commercial cultivar susceptible to root-knot nematode. All araçazeiro genotypes evaluated were resistant to the disease, with low reproduction factor (0.000 to 0.004) compared to cultivar Paluma (FR = 1,610). These results demonstrate that the araçazeiro genotypes have the potential to be used in the development of rootstocks resistant to guava decline.